Undaria pinnatifida a Rich Marine Reservoir of Nutritional and Pharmacological Potential: Insights into Growth Signaling and Apoptosis Mechanisms in Cancer. (18th August 2018) - Phull, Abdul Rehman; Kim, Song Ja
Abstract: Seaweeds are an important part of diet consumed in a different part of the world such as New Zealand, Ireland, Wales, and Asian countries including Korea, China, and Japan. In addition, seaweed is nutritious sources possessing health improving effects and therapeutic potential. Recently, one of the widely eaten seaweed species Undaria pinnatifida ( U. pinnatifida ) has got much attention because of its pharmacological properties for the prevention of various ailments, including cancer, inflammation, and other diseases. It is rich in all essential amino acids, physiologically significant fatty acids, vitamins, minerals, and has a variety of bioactive constituents which include fucoidan, carotenoids, and fucoxanthin. The present study reviews the nutritional aspects, key bioactivities specifically focusing on anticancer potential along with apoptosis and growth signaling mechanisms of U. pinnatifida or its constituents. It exhibited anticancer effects both in vitro and in vivo studies in a variety of experimental models. Due to a variety of pharmacological properties of U. pinnatifida can not only fulfilling nutritional necessities, but it can be used for treating, curing and preventing cancer.